Computational fluid dynamics studies on the induction period of crude oil fouling in a heat exchanger tube. (October 2020) - Yang, Junfeng
Highlights: A fouling model including foulant formation and ageing has been implemented in a CFD code. An interference factor was introduced to assess the interplay between fouling routes. Optimal operating conditions for heat exchangers include low t and high re numbers. Abstract: Fouling impairs the hydrodynamic and thermodynamic performance of crude oil pre-heat train exchangers in refineries. The very early stage of fouling, so-called induction period, containing inappreciable levels of fouling is poorly understood due to a lack of experimental data. To better understand this period and seek potential fouling mitigation strategies, a model is implemented in a computational fluid dynamics (CFD) code, which accounts for chemical reaction- and precipitation-driven fouling, turbulent flow, and ageing in a heat exchanger tube. Three-dimensional CFD simulations are carried out under various operating conditions to gauge the relative importance of the two fouling mechanisms, and provide direct predictions of deposition rates. The interaction between chemical and precipitation fouling processes is characterized using an "interference factor", introduced to evaluate the extent of suppression of the chemical mechanism and enhancement of precipitation. The results provide insights into the interaction of key mechanisms during the induction period (up to three seconds flow time) of fouling in crude oil heat exchangers and possible strategies for prolonging this near nil-fouling period.